2013
DOI: 10.1186/cc12926
|View full text |Cite
|
Sign up to set email alerts
|

Rapid molecular test (SeptiFast®) reduced time for adjustment of antibiotic treatment in comparison with conventional blood cultures in critically ill sepsis patients: a randomized controlled clinical trial (preliminary results)

Abstract: Background: We hypothesized that one single episode of acute kidney injury (AKI) reduces long-term survival compared with no acute kidney injury (No AKI) following recovery from critical illness. Materials and methods: A prospective cohort of 2,010 patients admitted to the ICU between 2000 and 2009 at a provincial referral hospital was followed to determine whether AKI influences long-term survival. Results: Of the 1,844 eligible patients, 18.4% had AKI stage 1, 12.1% had stage 2, 26.5% had stage 3, and 43.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The number of patients with therapy modification based on a positive diagnostic test was 4 out of 41 (9.8%) in the SeptiFast group and 5 out of 37 (13.5%) in the blood culture group. Rodrigues et al 100 reported a mean time to change in therapy of 580 minutes (9.7 hours) with SeptiFast, compared with 3007 minutes (50.1 hours) (p-value for the between-group difference = 0.004) for blood culture. The number of patients in whom an adjustment of treatment was performed was 6 out of 17 (35%) in the SeptiFast group and 7 out of 29 (24%) in the blood culture group.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of patients with therapy modification based on a positive diagnostic test was 4 out of 41 (9.8%) in the SeptiFast group and 5 out of 37 (13.5%) in the blood culture group. Rodrigues et al 100 reported a mean time to change in therapy of 580 minutes (9.7 hours) with SeptiFast, compared with 3007 minutes (50.1 hours) (p-value for the between-group difference = 0.004) for blood culture. The number of patients in whom an adjustment of treatment was performed was 6 out of 17 (35%) in the SeptiFast group and 7 out of 29 (24%) in the blood culture group.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
“…community, emergency department, hospital, intensive/critical care, general/ specialist) was not reported for nine SeptiFast studies, 44,65,69,72,88,98,100,105,110 or for one multitest SeptiFast and SepsiTest study 118 (confidential information has been removed). The setting across the remaining studies varied (see Table 4).…”
Section: Study Design Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations